2017
DOI: 10.1590/1983-1447.2017.01.63557
|View full text |Cite
|
Sign up to set email alerts
|

Saberes do enfermeiro para o cuidado no processo transfusional em recém-nascidos

Abstract: The identification of nurses' knowledge of blood transfusion, it is possible to promote their capacity for quality and safety of care related to the transfusion process in newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Intensive follow-up of patients in the first 10 minutes of transfusion was a point on which they demonstrated accurate knowledge. 17 Article 6 included 35 participating neonatologist nurses. The study proposal encompassed post-transfusion care, and, in this sense, participants demonstrated a lack of knowledge regarding the correct disposal of used transfusion bags.…”
Section: Resultsmentioning
confidence: 99%
“…Intensive follow-up of patients in the first 10 minutes of transfusion was a point on which they demonstrated accurate knowledge. 17 Article 6 included 35 participating neonatologist nurses. The study proposal encompassed post-transfusion care, and, in this sense, participants demonstrated a lack of knowledge regarding the correct disposal of used transfusion bags.…”
Section: Resultsmentioning
confidence: 99%
“…Although the study professionals did not report considerations about the recommended time for each type of blood component. As for the infusion speed, a study highlights that administration should be started slowly, making sure that the peripheral venous access is adequate and paying attention to the possible risks of circulatory overload [21].…”
Section: Discussionmentioning
confidence: 99%
“…Técnica de coleta de dados: questionário N6 I A10 22 Analisar o conhecimento do enfermeiro acerca do processo transfusional para o cuidado do recém-nascido na unidade de terapia intensiva neonatal.…”
Section: Estudo Descritivounclassified
“…-Notificar o evento adverso em caso de reação transfusional. 22 Fonte: elaborado pelos autores a partir dos dados da revisão, 2020. documento legal e justifica a necessidade do procedimento. Este precisa ser preenchido adequadamente, seguindo as normas.…”
Section: Pós-transfusãounclassified